ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL PELUANG PADA SISWA SMP KELAS IX DITINJAU DARI TAKSONOMI BLOOM - Riana Riana; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the difficulties of students in working on questions about opportunities in class IX Middle School students in one school in Nagreg. The research method used is a qualitative description method. The study was conducted with a sample of 27 students. The test questions given are in the form of 6 descriptive test questions that have a cognitive level based on Bloom's Taxonomy that has been validated both in content and empirical. Data processing techniques namely through data tabulation, then calculating of percentages and comparing the results of calculations with criteria. The results of the study state that students find it difficult to determine the empirical opportunity of an experiment and determine the sample space of an experiment at a high cognitive level (C6). Difficulties arise because students are unfamiliar with the concept, students do not understand the material, have not been able to conceptualize and analyze correctly, also weak mastery and understanding of existing concepts. So this indicates that there are still many students who have difficulty in solving the problem opportunity.